UPAYA PENINGKATAN MOTIVASI BELAJAR PAI BAGI SISWA MELALUI METODE PEMBELAJARAN ACTIVE LEARNING DI SDN NGLANDEYAN TAHUN PEMBELAJARAN 2023/2024 - Selfira; Siti Ulfa Zahrun N; Lauchatul Jannah; Dyah Candra Palupi; Santoso, Moch; Hakim, Ibnu (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2024)
The purpose of this research is to determine the role of parents in guiding or developing students, to find out what factors support and hinder the role of parents in improving student learning achievement, and to find out the role of parents in improving student learning achievement. This type of research is field research with a qualitative approach, data obtained through observation, documentation and interview methods. The research results showed that the role of parents in improving student learning achievement in the family has gone quite well. The role of student parents is: 1) Parents who create a comfortable and calm home environment as well as good communication between parents and children; 2) Parents of students can organize activities and understand the student's situation. Problems faced by parents Improving academic achievement at home include: limited facilities; Children are less interested in learning, children's relationship with the environment; 3) Providing facilities to improve children's achievements; 4) Parents involve children in activities related to their learning, such as: tutoring or tutoring; 5) Controlling children studying at home and getting children to be disciplined with time when doing all activities. In conclusion, the role of parents in improving the learning achievement of grade 3 students at MI Assalam Bajo is very good, covering several aspects of both the role and educational and social background of parents. The role and attention of parents is an important factor that can influence children's learning achievement.